Ricerche sul teatro classico spagnolo in Italia e oltralpe (secoli XVI-XVIII) - ANTONUCCI, Fausta; VUELTA GARCIA, Salome' (Studi e saggi, 2020)
At the height of its development and up to the eighteenth century, the Spanish classical theatre significantly contributed to the formation of the modern European theatre. Theatre texts and theatrical companies were in fact circulating outside the Iberian peninsula and the Spanish experience of theatre triggered literary debates and reflections that played a central role to the cultural history of Europe, from Neoclassicism to the beginnings of Romanticism. It is a complex phenomenon crossing linguistically and culturally diversified territories, and which therefore needs an inter- and multidisciplinary approach. We tried to respond to this need by involving scholars and researchers in the fields of Hispanic, French, Italian, history of entertainment and musicology for the drafting of this volume.